2007
DOI: 10.1016/j.chom.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Nonimmunodominant Regions Are Effective as Building Blocks in a Streptococcal Fusion Protein Vaccine

Abstract: Identification of antigens that elicit protective immunity is essential for effective vaccine development. We investigated the related surface proteins of group B Streptococcus, Rib and alpha, as potential vaccine candidates. Paradoxically, nonimmunodominant regions proved to be of particular interest as vaccine components. Mouse antibodies elicited by Rib and alpha were directed almost exclusively against the C-terminal repeats and not against the N-terminal regions. However, a fusion protein derived from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 31 publications
(64 reference statements)
4
46
0
Order By: Relevance
“…On the other hand, the immunogenic Alp1-specific site was most likely located in the N-terminal segment of Alp1, as some stretches of the bca and alp1 N termini showed considerable sequence divergencies, with the possibility of forming a structural basis for both the protein-specific epitope(s) and primer binding site(s) for both bca-and alp1-specific PCRs (6). These results have substantiated the assumption that both the repeat area and the N terminus of native Alp1 possess immunogenic sites, each site with distinctive specificity, similar to those of C␣ and R4 (Rib), demonstrated by immunization with recombinant constructs of stretches of the proteins (9,29). The location in the protein antigens of the Alp1/Alp2/Alp3 common site is not known with certainty, but location in the N termini seems likely.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…On the other hand, the immunogenic Alp1-specific site was most likely located in the N-terminal segment of Alp1, as some stretches of the bca and alp1 N termini showed considerable sequence divergencies, with the possibility of forming a structural basis for both the protein-specific epitope(s) and primer binding site(s) for both bca-and alp1-specific PCRs (6). These results have substantiated the assumption that both the repeat area and the N terminus of native Alp1 possess immunogenic sites, each site with distinctive specificity, similar to those of C␣ and R4 (Rib), demonstrated by immunization with recombinant constructs of stretches of the proteins (9,29). The location in the protein antigens of the Alp1/Alp2/Alp3 common site is not known with certainty, but location in the N termini seems likely.…”
Section: Discussionsupporting
confidence: 54%
“…An explanation for this could be that while the native Alp1-specific marker seemed to be immunodominant, a corresponding C␣-specific marker may be nonimmunodominant, an assumption supported by the results of other investigators (29). Thus, antisera raised against native C␣ or against other Alps tested for immunobiological function, including protective activity in experimental infections (14,21,28), may not have contained antibodies against N-terminal epitopes.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…It was recently reported that nonimmunodominant regions were effective as building blocks in a streptococcal fusion protein vaccine (42). Although CAT and GBD were suggested to be nonimmunodominant in this study, they nevertheless may be attractive vaccine targets.…”
mentioning
confidence: 83%
“…development and suggested the importance of analyzing major surface-exposed proteins for the presence of subregions that elicit protective immunity as a complement to the RV approach [65]. Additionally, the insolubility of many of the proteins tested by ELISA might also lead to false-negative titer-values, as it has been shown that linear epitopes are less likely to be immunodominant and elicit a good B-cell response if the protein possesses a higher-order structure [66].…”
Section: Discussionmentioning
confidence: 99%